2016
DOI: 10.1021/acscatal.6b00426
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Nature of Fe Species during Pyrolysis of the Fe-BTC MOF into Highly Active and Stable Fischer–Tropsch Catalysts

Abstract: In this combined in situ XAFS, DRIFTS, and Mössbauer study, we elucidate the changes in structural, electronic, and local environments of Fe during pyrolysis of the metal organic framework Fe-BTC toward highly active and stable Fischer–Tropsch synthesis (FTS) catalysts (Fe@C). Fe-BTC framework decomposition is characterized by decarboxylation of its trimesic acid linker, generating a carbon matrix around Fe nanoparticles. Pyrolysis of Fe-BTC at 400 °C (Fe@C-400) favors the formation of highly dispersed epsilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(150 citation statements)
references
References 69 publications
(119 reference statements)
12
137
0
1
Order By: Relevance
“…For the unpromoted samples, the particle size effect on the activity was less pronounced than for the promoted samples, in line with previously reported FTY values for a similar range of particle sizes produced by pyrolysis of F300 Fe-BTC at different temperatures 16 . These findings indicate that particle size is the key factor in Fe@C catalyst design, and this effect is even more pronounced in the K-promoted samples.…”
Section: Catalytic Testingsupporting
confidence: 91%
See 2 more Smart Citations
“…For the unpromoted samples, the particle size effect on the activity was less pronounced than for the promoted samples, in line with previously reported FTY values for a similar range of particle sizes produced by pyrolysis of F300 Fe-BTC at different temperatures 16 . These findings indicate that particle size is the key factor in Fe@C catalyst design, and this effect is even more pronounced in the K-promoted samples.…”
Section: Catalytic Testingsupporting
confidence: 91%
“…The similar pyrolysis behaviour for the Fe@C catalysts was confirmed by analysing the degree of carbonization, calculated from C/O ratios of the C matrix, indicating one molecule of CO 2 is removed from the framework next to an additional O molecule, assumed to be in the form of a water molecule. In previous work, we showed that the structure collapse by initial decarboxylation is followed by carboxylate side reactions, supposedly forming anhydride species as intermediates towards more graphite-like structures 16 . Additionally, higher C/O ratios were found on the surface than in the bulk, suggesting that surface C is more prone to releasing O from its structure.…”
Section: Characterization Of Fe@c Catalystsmentioning
confidence: 98%
See 1 more Smart Citation
“…16,17 In particular, MOF-mediated synthesis of iron-based FTO catalysts leads to exceptional performance in the synthesis of lower olefins from synthesis gas. [18][19][20] The effects of the addition of potassium promoters/additional carbon loading, 18 pyrolysis temperature, 19 and linker molecule structure/heteroatoms 20 on the catalysts properties have been investigated. However, the influence of the porosity of the MOF precursor on the iron/carbon catalysts has not been investigated but is likely to be crucial for the performance of the resulting catalysts.…”
Section: -10mentioning
confidence: 99%
“…Very few studies have reported the synthesis of Fe 3 C‐based catalysts from MOF precursors, probably because of two reasons. Firstly, carbonization of the Fe‐MOF mostly leads to a mixed‐phase product such as Fe 3 C, iron oxide, or metallic iron; this complicates unambiguous identification of the true active sites for the ORR. Secondly, the prepared catalysts do not have well‐defined nanostructures .…”
Section: Figurementioning
confidence: 99%